The Search for Accountability: United States v. McDonnell and the Fundamental Right to Honest Government. (2nd January 2018) - Roberts, Robert
Abstract : The U.S. Supreme Court in McDonnell v. United States (2016 ) vacated the conviction of a former Virginia governor for accepting bribes. The court found that arranging a meeting, calling or contacting another official, or hosting an event does not, by itself, rise to the level of an official act under the Hobbs Act and the mail and wire fraud statutes. This article argues that the Supreme Court's decision in McDonnell v. United States will make it much more difficult for federal prosecutors to prosecute state and local governments for helping private individuals gain preferential access to government decision-makers at the state or local level. The article also argues that the decision will put pressure on state legislatures to significantly tighten state ethics laws to stop this type of conduct that reduces public trust in government.